Franklin Ford Collection - Trudel, Dominique; De Maeyer, Juliette (mediastudies.press, 2023)
The American journalist Franklin Ford (1849-1918) is remembered for his ambitious (and stillborn) Thought News periodical, hatched with philosopher John Dewey. The Franklin Ford Collection, curated and introduced by Dominique Trudel and Juliette De Maeyer, takes in the full shambolic spread of Ford's thought, across news, politics, education, finance, and society at large. The collection includes nineteen documents-letters, leaflets, editorials, and treatises-with critical annotations from Trudel and De Maeyer. The works, many unpublished or rarely circulated, illustrate the core themes that animated Ford's career, including his sweeping program of press reform and his thoughts on the interconnected flows of money, transportation, and communication.